Laboratory Manual for Chemistry : - Vincent, John B. (Pearson, 2008)
This comprehensive laboratory manual contains 34 experiments with a focus on real-world applications. These experiments were written specifically to correspond with the first edition of Chemistry: A Molecular Approach by Nivaldo J. Tro. Each experiment covers one or more topics discussed within a chapter of the textbook, with the primary goal of helping students understand the underlying concepts covered in the lecture course and presenting this material in a way that is interested and exciting to the students